Pengaruh Terdeteksinya Kecurangan, Keadilan Pajak, Tarif Pajak, dan Kecenderungan Personal terhadap Tax Evasion pada Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Pratama Surabaya Gubeng - Masruroh, Afi; Riyadi, Slamet (Business and Investment Review, 2025)
The purpose of this research is to explore the impact of the possibility of fraud detection, tax fairness, tax rates, and personal tendencies on tax evasion among individual taxpayers at KPP Pratama Surabaya Gubeng. Applying a quantitative method, utilizing multiple regression analysis was conducted utilizing SPSS26, utilizing primary data collected through questionnaires from 100 respondents. The results suggest that that the possibility of fraud detection and tax fairness do not significantly influence tax evasion. However, tax rates and personal tendencies have a significant impact on tax evasion. Additionally, all four variables collectively play a significant role in influencing tax evasion. This research offers important understanding of the factors affecting tax evasion and may Providing a foundation for creating more effective tax policies.